Economic evaluation of sintilimab plus chemotherapy vs. pembrolizumab plus chemotherapy for the treatment of first-line advanced or metastatic squamous NSCLC - Chen, Pingyu; Wang, Xintian; Zhu, Shengwen; Li, Hongchao; Rui, Mingjun; Wang, Yingcheng; Sun, Haikui; Ma, Aixia (Frontiers in Public Health, 2022)
Background and Objective: Sintilimab has superior efficacy and safety in patients with advanced or metastatic squamous non-small cell lung cancer (NSCLC), but its cost-effectiveness in China is unclear. This study is to evaluate the cost-effectiveness of sintilimab plus chemotherapy versus pembrolizumab plus chemotherapy for locally advanced or metastatic squamous NSCLC in China. Methods: From the perspective of the Chinese health system, the partitioned survival model with three health states was established in a 3-week cycle and a lifetime time horizon. The two-stage method was used to estimate the overall survival hazard rations to avoid the bias by crossover design in Orient-12 and Keynote-407 studies. The anchored matching adjusted indirect comparison method (MAIC) was used for indirect comparison based on the individual patient data from Orient-12 and public published Keynote 407 study due to the lack of head-to-head clinical trials. Only direct medical costs were included, and utilities were derived from the published literatures in base-case analysis. Sensitivity analysis was also performed to verify the robustness of the model results. In addition, the scenario analysis where the utilities were derived from the QLQ-C30 scale in Orient-12 by mapping to the EQ-5D-5L was carried out to explore the uncertainty of results. Results: Compared with the pembrolizumab, sintilimab incurred lower lifetime cost ($12,321 vs. $36,371) and yielded less Quality-adjusted life-years (QALYs) (0.9902 vs. 1.0085), which resulted in an incremental cost-effectiveness ratio (ICER) of $1,314,208/QALY. Sintilimab strategy is a cost-effectiveness option under the willingness-to-pay (WTP) of 1-3 times the GDP per capita in China ($11,250/QALY~$33,749/QALY). The utility value of the post-progression was the most drivers in the deterministic sensitivity analysis (DSA) . According to the probabilistic sensitivity analysis (PSA), sintilimab was 100% cost-effective when the WTP was 1-3 times of China’s per capita GDP. The results of the scenario analysis showed that sintilimab group obtained more QALYs (1.2319 vs. 1.1815) and lower costs ($12,321 vs. 36,371), which implied that the sintilimab + chemotherapy may dominate the pembrolizumab + chemotherapy. Conclusion: Compared with pembrolizumab + chemotherapy, sintilimab + chemotherapy is more cost-effective for first-line treatment in Chinese patients with locally advanced or metastatic squamous NSCLC.